2014
DOI: 10.3233/ch-131743
|View full text |Cite
|
Sign up to set email alerts
|

Physostigmine reverses disturbances of the intestinal microcirculation during experimental endotoxemia

Abstract: Intestinal microcirculatory disturbances play an important role in the pathophysiology of sepsis. A neural antiinflammatory pathway has been suggested as a potential target for therapy that may dampen systemic inflammation. The aim of this study is to investigate the effects of physostigmine, a cholinesterase inhibitor, on the intestinal microcirculation and vascular contractility in experimental endotoxemia. Endotoxemia was induced in Lewis rats by intravenous lipopolysaccharide (LPS) administration. Animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Protective effects by PHY have already been described in various experimental models of injury, among others during sepsis/systemic inflammation,1517 hemorrhagic shock,1821 and ischemia–reperfusion injury 2426. However, in all these experimental animal studies, PHY has been administered in a prophylactic manner or early after the injury.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Protective effects by PHY have already been described in various experimental models of injury, among others during sepsis/systemic inflammation,1517 hemorrhagic shock,1821 and ischemia–reperfusion injury 2426. However, in all these experimental animal studies, PHY has been administered in a prophylactic manner or early after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of PHY in counteracting harmful actions of sepsis1517 are primarily attributed to its direct anti-inflammatory capabilities through the so-called cholinergic anti-inflammatory pathway as described by Tracey et al2830 Cholinesterase inhibition by PHY or its synthetic analog neostigmine has been described to improve survival and inflammation-related organ dysfunction if applied before or directly after the induction of sepsis or systemic inflammation:10,16 Hofer et al demonstrated that both PHY and neostigmine improve survival in a murine CLP model, when treatment started directly after CLP and was continued three times daily for 3 days (single dose: 80 µg/kg) 16. Kalb et al already showed that PHY and neostigmine prevent neuroinflammation in a rat LPS model, when treatment started 5 minutes before the LPS application (single dose: 100 µg/kg) 10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations